Preparedness of undergraduate dental students: a national study / Suib F.N. ... [et al.] - F.N., Suib; I.E.S., Mohamed Ismail; L.T., Younis; N.N., Bakri; M.I., Abu Hassan (Faculty of Dentistry, Universiti Teknologi MARA, 2021)
To evaluate the self-perceived preparedness of final year undergraduate dental students in Malaysia and to compare the difference of preparedness level of final undergraduate student in public and private universities. A cross-sectional questionnaire study was conducted using a validated questionnaire, Dental Undergraduates Preparedness Assessment Scale (DU-PAS) and no samplings were involved. The questionnaire was distributed via University presentative of each university from MDSA in the form of online and written questionnaire. The data were analysed using SPSS version 23. Results: 239 students responded to this study. Responses revealed that student felt adequately prepared to carry out simple clinical procedures such as taking consent (88.3%), tooth-coloured fillings (87.4%), non-surgical periodontal treatment (86.6%), do proper history taking (85.8%), bitewing radiograph (84.1%) and communication skills (69.9%). However, low levels of scores were reported on ability to do an amalgam restoration (12.1%), endodontics treatment especially multi-rooted tooth (9.6%), crowns (9.2%), referral for suspected oral cancer (31.8%), research skills (15.1%) and raising concerns regarding inappropriate behaviour of colleagues (7.9%). There was significant difference between the level of preparedness of final undergraduate student in public and private universities. This is the first study of self-perceived preparedness of final year undergraduate students in Malaysia. The results showed that the self-perceived preparedness of final year student was satisfactory for a range of clinical and effective skills. However, several areas of weaknesses were identified which underscore the need for additional training and consolidation.